Pengujian Usability Website Portal Mahasiswa IPB Menggunakan Metode System Usability Scale (SUS) - Wafa, Saniyyah; Maryadi, Muhammad Rahmat; Mahendar, Ibnu Aqil; Fami, Amata; Wahyoedi5, Bontisesari (Universitas Multi Data Palembang, 2024)
The IPB Student Portal is a platform that plays an important role in providing information to students about the academic and administrative aspects of the university environment. Improving the usability of this website is a primary need for efficiency and user satisfaction. This study uses the System Usability Scale (SUS) to evaluate the IPB Student Portal website. The research method involves usability testing with a questionnaire based on ten predetermined usability criteria. Respondents to the survey were active students who used the IPB Student Portal website. Research results show that the IPB student portal has an adjective rating (Ok) with a SUS score of 56.3. To improve the user experience of the IPB student portal, it is necessary to improve user controls, simplify navigation, reduce system errors, speed up document control, train users and provide active feedback channels..